2016
DOI: 10.3892/or.2016.5202
|View full text |Cite
|
Sign up to set email alerts
|

Myofibroblast distribution is associated with invasive growth types of colorectal cancer

Abstract: Both the invasive growth types of colorectal cancer (CRC) and the number of myofibroblasts have been associated with histopathological factors such as lymph node and liver metastasis, and local recurrence. However, there are few studies, that have assessed the association between invasive growth type and myofibroblast distribution in CRC. We aimed to evaluate the relationship between the clinicopathological factors of CRC and two invasive growth types, the expanding and infiltrating types. We categorized 150 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…A recent report has shown the association of multiple CAF markers, namely α-SMA, collagen I, and platelet-derived growth factor receptor-beta (PDGFR-β), which are widely distributed in the stroma, with high venous invasion in advanced CRC (Nishishita et al, 2018). This supports a previous observation of the correlation of α-SMA positive and desmin negative myofibroblasts in advanced CRC with malignancy potential (Takatsuna et al, 2016). On the contrary, the expression of podoplanin in CAFs indicates a favorable prognosis of CRC (Choi et al, 2013), although other reports have shown podoplanin expression as a marker for an unfavorable prognosis (Kitano et al, 2010;Schoppmann et al, 2013).…”
Section: Introductionsupporting
confidence: 79%
“…A recent report has shown the association of multiple CAF markers, namely α-SMA, collagen I, and platelet-derived growth factor receptor-beta (PDGFR-β), which are widely distributed in the stroma, with high venous invasion in advanced CRC (Nishishita et al, 2018). This supports a previous observation of the correlation of α-SMA positive and desmin negative myofibroblasts in advanced CRC with malignancy potential (Takatsuna et al, 2016). On the contrary, the expression of podoplanin in CAFs indicates a favorable prognosis of CRC (Choi et al, 2013), although other reports have shown podoplanin expression as a marker for an unfavorable prognosis (Kitano et al, 2010;Schoppmann et al, 2013).…”
Section: Introductionsupporting
confidence: 79%
“…High levels of α-SMA subtraction (P=0.002), collagen I (P=0.040), and PDGFR-β (P=0.040) expression areas tended to be associated with high venous invasion. α-SMA positive and desmin negative myofibroblasts in the advanced colorectal cancer is associated with malignant potential in previous study ( 16 , 17 ). Serum levels of Collagen I degradation telopeptide are correlated with staging and poor disease-free survival of colorectal patients ( 19 ).…”
Section: Discussionmentioning
confidence: 60%
“…Previous reports were accomplished about each CAF ( 13 , 16 19 ), but did not provided the information about the comparison of each CAF. We captured immunohistochemical staining images, and adjusted phases in each case by using Adobe Photoshop software (Adobe ® Photoshop ® CC 2014 ® ; USA) for image registration, and compared the different antibodies in the same field.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially intriguing in CRC, where there is an excess of local TGF-β in the majority of tumours (Calon et al, 2012). The histological organisation of CAFs and cancer cells provides certain clues, with the co-localisation of myofibroblasts and invasive carcinoma cells reported in various solid tumours (Kawashiri et al, 2009;Öhlund et al, 2017;Takatsuna et al, 2016). In CRC, the most lethal CMS4 subtype produces a stroma rich in α-SMA-positive myofibroblasts (Becht et al, 2016;Guinney et al, 2015).…”
Section: Introductionmentioning
confidence: 99%